Safety Goggles Myopi as a Worker Protector with Myopic Eye Complaints - Naufal Ilham Saputra; Ramadhani, Husnul Kirom; Violin Margaretha Puspita Ningrum; Amrina Rosyadah; Muslikha Nourma Rhomadhoni (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
ABSTRACT   The number of workers who have near-sightnedness and is supported by a lack of compliance in use of PPE for comfort reasons causes the potential for work accidents. This research aimed to reduce the number of eye injuries and become an innovation in safety glasses and PPE for workers complaints of myopia. This study used an analytical descriptive method with a cross-sectional study design, which was carried out from June to October 2022. The total respondents in this study were 60 respondents. Furthermore, this study used an instrument, namely a survey questionnaire through a comprehensive Google Form. From the survey, 55% of respondents used glasses, 53.3% of respondents experienced complaints of myopia, 18.3% of respondents have worn glasses before work, 20% of respondents were required to wear protective glasses while working, and 80% of respondents showed interest in "Safety Goggles Myopi". The test results at the laboratory of Nahdlatul Ulama University Surabaya using the Lutron Type-340A UV Metershowed that "Safety Goggles Myopi" is effective in reducing exposure to UV radiation from the sun and welding rays to 0 mW/m2. Additionally, "Safety Goggles Myopi" also has a concept of glasses with 3 in 1 lenses that are comfortable and practical when used. Through these results, the idea of PPE innovation entitled "Safety Goggles Myopi" is appropriate to reduce the number of work accidents, increase compliance in the use of PPE protective glasses in the workplace, especially for workers who have near-sightedness, and improve the implementation of K3’s culture in Indonesia. Keywords: Eye complaints, K3 culture, near-sightedness, PPE Use, safety goggles myopi, workers, work accidents.